Implementasi Model Pembelajaran Hybrid Learning di MIN 1 Kota Madiun - Nurul Malikah; Yossima Nizar Zulfikar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to analyze the application of the hybrid learning method at MIN 1 Madiun City. In the current digital era, the effectiveness of learning methods is increasingly becoming the focus of research. Analysis of the implementation of learning methods is important to provide recommendations for improving learning in the future. This research uses a qualitative approach with data collection techniques through interviews and literature study. The main focus of this research is the analysis and evaluation of the implementation of the hybrid learning method at MIN 1 Madiun City. The research results show that teachers at MIN 1 Madiun City have utilized various digital technologies, including the use of online learning platforms, to implement hybrid learning methods. This technology enables integration between face-to-face learning and online learning, providing flexibility and better access for students. This research also found that implementing the hybrid learning method can increase student engagement and provide a more interactive and effective learning experience. However, this research also identified several challenges, such as limited access to technology for some students and the need to increase digital competence for teachers. It is hoped that the results of this research can provide an important contribution in understanding the effectiveness of the hybrid learning method at MIN 1 Madiun City and help improve the quality of education at the madrasa. Thus, this research can be a reference for other educational institutions that wish to adopt similar learning methods.